2019
DOI: 10.1371/journal.pone.0209748
|View full text |Cite
|
Sign up to set email alerts
|

An analog of glibenclamide selectively enhances autophagic degradation of misfolded α1-antitrypsin Z

Abstract: The classical form of α1-antitrypsin deficiency (ATD) is characterized by intracellular accumulation of the misfolded variant α1-antitrypsin Z (ATZ) and severe liver disease in some of the affected individuals. In this study, we investigated the possibility of discovering novel therapeutic agents that would reduce ATZ accumulation by interrogating a C. elegans model of ATD with high-content genome-wide RNAi screening and computational systems pharmacology strategies. The RNAi screening was utilized to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The CHO cell model faithfully recapitulates the handling of mutant variants of α 1 ‐antitrypsin seen in other cellular models [23,53], with the benefits of inducible and titratable expression and robust characteristics in cell culture. We confirmed our findings using an iPSC model of Z α 1 ‐antitrypsin deficiency [35,36], which showed similar half‐times for the clearance of soluble and insoluble polymers.…”
Section: Discussionmentioning
confidence: 99%
“…The CHO cell model faithfully recapitulates the handling of mutant variants of α 1 ‐antitrypsin seen in other cellular models [23,53], with the benefits of inducible and titratable expression and robust characteristics in cell culture. We confirmed our findings using an iPSC model of Z α 1 ‐antitrypsin deficiency [35,36], which showed similar half‐times for the clearance of soluble and insoluble polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the induction of autophagy in mice by rapamycin reduced liver alpha1-ATZ aggregation and liver injury[ 582 , 586 - 589 ]. These findings have been repeated and verified when enhancement of autophagy[ 590 ] with either carbamazepine[ 591 ], gene transfer of the autophagy regulator TFEB[ 592 ] or an analog of glibenclamide[ 593 ] reduced the toxic protein. Recent preclinical studies have also demonstrated that an exogenous bile acid like norursodeoxycholicacid may be clinically useful in this condition[ 594 , 595 ].…”
Section: Inherited Metabolic Diseasesmentioning
confidence: 89%
“…Analogous to what has been observed in humans, the ATM model displayed normal secretion of the protein into the intestinal lumen, whereas the ATZ disease model developed protein accumulation in the ER as well as increased autophagy in these cells ( Gosai et al, 2010 ). Given its faithful recapitulation of disease phenotypes, this ATD model was used in a high-throughput, genome-wide RNAi screen to identify genes that, when depleted, significantly affected ATZ accumulation in the intestine of these animals ( O'Reilly et al, 2014 ; Wang et al, 2019 ). This screening strategy identified 54 modifier genes, which were also verified orthologs of human genes.…”
Section: Elegans For Use In Drug Discoverymentioning
confidence: 99%